ANALISIS YURIDIS PUTUSAN HAKIM TERHADAP NOTARIS YANG MERUBAH ISI MINUTA AKTA PERJANJIAN TANPA PERSETUJUAN PARA PIHAK (Studi Kasus Perkara Nomor 42/Pdt.g/2013/Pn.pbr) - KARTIKA WILY; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
An institution with its devotees is assigned bythe Law requires such or desired by the public to produce written evidence that has authentic powers. This makes the Notary Institutions very necessary. Notary has an obligation to make deed in the form of Original of the deed. This deeds are kept as part of the Notary Protocol. From that deeds, the Notary is obligated to issue Grosse Deed, Official duplicate copy of the deed and Extract of the deedto the person directly concerned with the deed, heirs, or other person obtaining rights, unless otherwise provided by law. In order to prevent misuse of the trust given by the Law to Notary, it must be ensured the rights and obligations of the parties for the sake of certainty, order and legal protection for the interested parties as well as the society as a whole. Therefore it is necessary to supervise the task of Notary always in accordance with the rules of the underlying law. The Judge through the decision of a case of change of the Original of the deed shall contain the grounds and grounds of the decision, containing certain articles of the relevant legislation or source of the unwritten law as the basis for judgment and the determination and decision shall contain judicial judgment based on the right legal basis and correct. The purpose of writing this thesis are to know; firstly to know the legal force against the Deed of Cooperation Agreement No. 149 in Case Number 42/Pdt.g/2013/Pn.pbr. Secondly, to find out the civil ruling imposed has been in accordance with the sense of justice.This research is normative law research or literature research. The research data is obtained from literature research using juridical approach method, which is analyzing the problem from the point of view or according to the law or the applicable law. This research is conducted by examining primary data such as case file with Case Study Case Number: Number 42/Pdt.g/2013/Pn.pbr. This research is Descriptive Research which purpose is to describe or illustrate clearly and in detail.From the research there are two main points that can be concluded; Firstly, the deed may be canceled because it does not complywith the subjective element of disagreement of the parties regarding the contents of the cooperation agreement. The agreement is null and void, because it does not meet the objective requirement which is a valid requirement of the agreement. Therefore the Notary can be held accountable by law and the code of ethics of the Notary profession. Secondly, the Judge takes little consideration of the evidence and intentions of the parties in making such a deed. The legal certainty set forth in the judge's decision is a result based on judicial facts relevant to the jurisdiction and considered with conscience.Keywords: Decision Analysis - Original of the deed - The Parties